Microorganism penetration in dentinal tubules of instrumented and retreated root canal walls. In vitro SEM study - Saad Al-Nazhan; Alaa Al-Sulaiman; Fellwa Al-Rasheed; Fatimah Alnajjar; Bander Al-Abdulwahab; Abdulhakeem Al-Badah (Korean Academy of Conservative Dentistry, 2014)
Objectives This in vitro study aimed to investigate the ability of Candida albicans (C. albicans) and Enterococcus faecalis (E. faecalis) to penetrate dentinal tubules of instrumented and retreated root canal surface of split human teeth. Materials and Methods Sixty intact extracted human single-rooted teeth were divided into 4 groups, negative control, positive control without canal instrumentation, instrumented, and retreated. Root canals in the instrumented group were enlarged with endodontic instruments, while root canals in the retreated group were enlarged, filled, and then removed the canal filling materials. The teeth were split longitudinally after canal preparation in 3 groups except the negative control group. The teeth were inoculated with both microorganisms separately and in combination. Teeth specimens were examined by scanning electron microscopy (SEM), and the depth of penetration into the dentinal tubules was assessed using the SMILE view software (JEOL Ltd). Results Penetration of C. albicans and E. faecalis into the dentinal tubules was observed in all 3 groups, although penetration was partially restricted by dentin debris of tubules in the instrumented group and remnants of canal filling materials in the retreated group. In all 3 groups, E. faecalis penetrated deeper into the dentinal tubules by way of cell division than C. albicans which built colonies and penetrated by means of hyphae. Conclusions Microorganisms can easily penetrate dentinal tubules of root canals with different appearance based on the microorganism size and status of dentinal tubules.